2013
DOI: 10.1108/imr-03-2012-0058
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative enquiry into the appropriation of mobile telephony at the bottom of the pyramid

Abstract: Purpose – The paper aims to analyse bottom of the pyramid (BoP) customers’ (e.g. Bangladeshi farmers) use and appropriation of mobile telephony and to critically identify a suitable research strategy for such investigation. Design/methodology/approach – Concentrated ethnographic immersion was combined with both methodological and investigator triangulation during a four-month period of fieldwork conducted in Bangladeshi villages to obtain more robust findings. Concentrated immersion was required to achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(17 citation statements)
references
References 47 publications
0
15
0
2
Order By: Relevance
“…Although there has been considerable research on the mobile telephony sector in recent times, the majority of these studies focus on the uses to which people put their phones, while others have looked at the impact of mobile phones on people's businesses and social relations (Boadi et al, 2007;Overå, 2008;Brouwer, 2010;Essegbey & Frempong 2011;Porter et al, 2012;Lal Dey et al, 2013). A few studies have also documented the activities of solo entrepreneurs who import mobile phones from Hong Kong to Africa (Yu & Kwan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although there has been considerable research on the mobile telephony sector in recent times, the majority of these studies focus on the uses to which people put their phones, while others have looked at the impact of mobile phones on people's businesses and social relations (Boadi et al, 2007;Overå, 2008;Brouwer, 2010;Essegbey & Frempong 2011;Porter et al, 2012;Lal Dey et al, 2013). A few studies have also documented the activities of solo entrepreneurs who import mobile phones from Hong Kong to Africa (Yu & Kwan, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Any applications of IoT-based innovation would take into account existing social paradigms among the target consumers viz. social acceptance [22], technological awareness [23] and consumer need [24]. This co-operative design process would also aid in the distribution of the technology among the consumers [25].…”
Section: Approach and Objectivesmentioning
confidence: 99%
“…Most of the studies in this third group deploy qualitative research methods for assessing the digital divide. The utility of qualitative methods is in gleaning more incisive descriptions about the participants' behaviour, especially towards their use of ICTs (Dey, Binsardi, Prendergast, & Saren, 2013). By the early-2000s, the term appropriation was beginning to take on more complex meanings than just access or usage, because the usage of ICTs has become a key part of our everyday lives (Karnowski, 2009).…”
Section: ) Studies On Appropriation Of Ictsmentioning
confidence: 99%
“…Different meanings for different participants. Specifically, the studies in this group found that using a computer and or the internet, hold varying connotations for different groups of users, and these meanings change with one's age, physical, social, emotional, and cognitive development (Dey et al, 2013;Dey, Newman, & Prendergast, 2011;Facer, Furlong, Furlong, & Sutherland, 2003;Mackay & Gillespie, 1992;Stewart, 2003). In presenting his digital divide model, Selwyn (2004) explained that appropriation is a "meaningful use of ICT…where the 'user' exerts a degree of control and choice over the technology and its content, thus leading to a meaning, significance and utility for the individual concerned."…”
Section: ) Studies On Appropriation Of Ictsmentioning
confidence: 99%
See 1 more Smart Citation